AKTIVITAS ANTIBAKTERI MADU TERHADAP BAKTERI MULTI DRUG RESISTANT Salmonella typhi DAN METHICILLIN-RESISTANT Staphylococcus aureus - Rahma Asriani Panjaitan; Sri Darmawati; Muhammad Evy Prastiyanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This study aimed to analyze the antibacterial activity of Palm oil Honey against Multi  Drug  Resistant  Salmonella  typhi  and  Methicillin-Resistant Staphylococcus aureus by concentration 50%, 60%, 70%, 80%, 90% and 100%. This  research  was  an  experimental  test  with  Posttest  Only  Control  Group Design in an in vitro manner using well diffusion method techniques. The well diffusion method used MHA which made by the well of 5 mm diameter and inserted 200 µ L sample then incubated 35 ± 20C for 24 hours. The results of the study showed the antibacterial activity of Palm oil Honey with zone inhibition against MDR S.typhi 11.4 mm (concentration 90%), 13.4 mm (concentration 100%) and against MRSA 11.7 mm (concentration 100%). The results of zone inhibition of Palm oil honey with concentration 100% against MDR S.typhi was larger than the  zone inhibition  against MRSA. The palm oil honey inhibition zone  against  S.typhi  MDR  bacteria  compared  with  sulfamethoxazole  (SXT) antibiotics with 25 mm inhibition zones was included in the intermediate category and the palm oil honey inhibition zone against MRSA bacteria compared with Tetracycline (TE) antibiotics with 23 mm inhibition zone was included in resistant category. Keywords: Antibacterial Activity, MDR S. typhi, MRSA, Honey, Inhibition Zone